1998
DOI: 10.1046/j.1365-8711.1998.01781.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling photospheric magnetoconvection

Abstract: The increasing power of computers makes it possible to model the nonlinear interaction between magnetic elds and convection at the surfaces of solar-type stars in ever greater detail. We present the results of idealized numerical experiments on twodimensional magnetoconvection in a fully compressible perfect gas. We rstvary the aspect ratio of the computational box and show that the system runs through a sequence of convective patterns, and that it is only for a su ciently wide box( 6) that the ow becomes inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 24 publications
9
37
0
Order By: Relevance
“…This means that the size of the grains decreases and their lifetime increases the deeper they are located in the umbra. This is in good agreement with the model simulations of Weiss et al (1996) and Blanchflower et al (1998) if it is assumed that the magnetic field strength is higher in the inner end of the light bridge than in its outer end. Measurements of Rüedi et al (1995) show that the field strength in SLBs is about 1500 G lower than in the surrounding umbra.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…This means that the size of the grains decreases and their lifetime increases the deeper they are located in the umbra. This is in good agreement with the model simulations of Weiss et al (1996) and Blanchflower et al (1998) if it is assumed that the magnetic field strength is higher in the inner end of the light bridge than in its outer end. Measurements of Rüedi et al (1995) show that the field strength in SLBs is about 1500 G lower than in the surrounding umbra.…”
Section: Resultssupporting
confidence: 88%
“…8). This result agrees very well with numerical simulations of Weiss et al (1996) and Blanchflower et al (1998), who have shown that the structure of the convective cells is strongly dependent on the magnetic field strength.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Numerical simulations of magnetoconvection in regions of large horizontal extent exhibit a phenomenon known as flux separation, where the convection cells and magnetic field rearrange spontaneously into areas where there is vigorous convection and weak magnetic field and other areas where the magnetic field is strong and the convection is reduced [5,9,10]. In its most extreme form, this process leads to the formation of "convectons" [11,12], which are isolated, stationary convection cells surrounded by practically stationary regions of strong magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…We wonder if the individual magnetic fibril is the basic mag netic entity rather than the mean field conventionally used in dynamo theory. The effect sometimes called "turbulent diamagnetism" (Blanchflower, Rucklidge, and Weiss, 1998; concentrates the magnetic field into regions of weak tur bulence and may play a role in forming the fibrils. The continual stretching of a fibril caught up in the convective flow and nonuniform rotation would continually intensify the field of the fibril.…”
Section: Fibril Magnetic Fieldsmentioning
confidence: 99%